2013
DOI: 10.1175/jcli-d-11-00687.1
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Statistical Downscaling Techniques for Their Robust Application under Climate Change Conditions

Abstract: The performance of Statistical Downscaling (SD) techniques is critically re-assessed with respect to their robust applicability in climate change studies. To this aim, in addition to standard accuracy measures and distributional similarity scores, we estimate the robustness of the methods under warming climate conditions working with anomalous warm historical periods. This validation framework is applied to intercompare the performance of twelve different SD methods (from the analogs, weather typing and regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
1
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 49 publications
7
200
1
5
Order By: Relevance
“…For this study, we chose to select the predictors out of the nearest grid point of the atmospheric reanalysis data set, which is a common approach in downscaling studies (e.g. Gutiérrez et al, 2013;Hofer et al, 2012Hofer et al, , 2015. It prevents dubious correlations with remote indices and ensures that the local glacier features are indeed related to the local atmospheric state (from the coarse data set perspective).…”
Section: Atmospheric Predictorsmentioning
confidence: 99%
“…For this study, we chose to select the predictors out of the nearest grid point of the atmospheric reanalysis data set, which is a common approach in downscaling studies (e.g. Gutiérrez et al, 2013;Hofer et al, 2012Hofer et al, , 2015. It prevents dubious correlations with remote indices and ensures that the local glacier features are indeed related to the local atmospheric state (from the coarse data set perspective).…”
Section: Atmospheric Predictorsmentioning
confidence: 99%
“…In most downscaling studies, no optimisation of the predictor domains has been performed, and only a few of them have tested even a handful of different domains (Timbal and McAvaney, 2001;Timbal et al, 2003;Gutiérrez et al, 2013). Timbal and McAvaney (2001) especially found that choosing an informative predictor domain is an important issue for the analogue selection.…”
Section: Predictor Domains: Optimisationmentioning
confidence: 99%
“…This algorithm is potentially applicable in other contexts. This study has already shown that it could be applied at different target locations, but one may also think of considering another predictand, such as minimum or maximum temperature (Gutiérrez et al, 2013), or optimising the spatial domain of other predictors. As a result, this algorithm could be perfectly applied to another type of statistical downscaling method.…”
Section: An Algorithm To Provide Near-optimum Predictor Domainsmentioning
confidence: 99%
“…Hewitson and Crane 2006;Jeong et al 2012) and the associated issues. Reviews of the methods outlined in Table 1 may be found in, for example, Bürger et al 2012;Gutiérrez et al 2013;Christensen et al 2007).…”
Section: Downscaling Approachesmentioning
confidence: 99%